2013
DOI: 10.1021/pr400224s
|View full text |Cite
|
Sign up to set email alerts
|

Combined N-Glycome and N-Glycoproteome Analysis of the Lotus japonicus Seed Globulin Fraction Shows Conservation of Protein Structure and Glycosylation in Legumes

Abstract: Legume food allergy, such as allergy toward peanuts and soybeans, is a health issue predicted to worsen as dietary advice recommends higher intake of legume-based foods. Lotus japonicus (Lotus) is an established legume plant model system for studies of symbiotic and pathogenic microbial interactions and, due to its well characterized genotype/phenotype and easily manipulated genome, may also be suitable for studies of legume food allergy. Here we present a comprehensive study of the Lotus N-glycoproteome. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 61 publications
(123 reference statements)
0
24
0
Order By: Relevance
“…Mass spectrometry (MS)‐based N ‐glycome profiling of Lotus japonicus seeds identified a total of 19 N ‐glycan structures spanning the full spectrum of high mannose, complex and paucimannosidic type N ‐glycans (Dam et al ., ). This observation indicated that Lotus japonicus possesses a typical plant N ‐glycan maturation pathway (Figure S1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mass spectrometry (MS)‐based N ‐glycome profiling of Lotus japonicus seeds identified a total of 19 N ‐glycan structures spanning the full spectrum of high mannose, complex and paucimannosidic type N ‐glycans (Dam et al ., ). This observation indicated that Lotus japonicus possesses a typical plant N ‐glycan maturation pathway (Figure S1).…”
Section: Resultsmentioning
confidence: 97%
“…To verify the altered N ‐glycosylation of the generated Lotus japonicus mutants, N ‐glycans released from their carrier proteins were characterised from seed extracts using PGC‐LC‐MS/MS. As expected, the N ‐glycan profile of wild type seed proteins, which included 24 N ‐glycan structures spanning 18 monosaccharide compositions, strongly resembled our previously reported profile of Lotus japonicus (Dam et al ., ) (see Table S2 for details of the identified N ‐glycans). The N ‐glycan type distribution of the wild type proteins differed in general from the distribution of the mutant proteins (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Outside the vertebrate subphylum, invertebrates such as Caenorhabditis elegans (16,18,(22)(23)(24) and Drosophila melanogaster (15,17,25,26), plants (27), and other "lower" organisms (28) abundantly produce protein paucimannosylation. Paucimannose synthesis in these species is facilitated by high ␤-Nacetylhexosaminidase activity, allowing partial suppression of the complex N-glycan biosynthetic route.…”
mentioning
confidence: 99%
“…N- glycosylation is also involved in food allergy, as several identified, N- glycosylated albumin proteins in wheat shared high sequence similarities with known food allergens [22]. Glycoproteomic characterization has also been attempted in cotton and various bio-fuel grasses and trees [17,19,21,23,28]. To the best of our knowledge, the identification of 242 glycosites on 191 proteins in the current study represents the largest scale profiling of glycoproteome in crops so far (S3 Table).…”
Section: Discussionmentioning
confidence: 99%